Assessing the Impact of the October 2020 Capena Earthquake on the Lago Puzzo Sinkhole (San Martino Valley, Rome, Italy): Seismological, InSAR, and Geophysical Evidence of Possible Causal Relationships - R. De Ritis; G. Rotella; C. Tolomei; G. Calderoni; F. Marra; A. Argentieri; P. Vitali; M. Fabiani; M. Chiappini; C. Doglioni (Pure and Applied Geophysics, 2025)
In October 2020, a low-magnitude earthquake struck near the village of Capena, approximately 30 kilometers north of Rome. This seismic event was particularly remarkable due to its shallow hypocenter and the complete absence of aftershocks. Additionally, both during and after the event, residents reported hearing loud rumbling noises on multiple occasions in the village and surrounding rural areas. The earthquake's epicenter is located in a sinkhole-prone region intersected by major infrastructure, including a high-speed railway, high-voltage power lines, and a provincial road. Given these conditions, public authorities and regional Civil Protection agency closely monitored the area, prompting a comprehensive investigation. The study adopted an interdisciplinary approach to assess the stability of sinkhole-prone zones and identify any geological changes potentially triggered by the earthquake. A key focus of the research was the "Lago Puzzo," a well-documented example of multiphase, still active, sinkhole evolution within the San Martino Valley, alongside other similar extinct features in the area. The investigation integrated three primary methodologies: spectral analysis of seismic data to characterize the October 2020 event; remote sensing (SAR) using InSAR analysis to map ground displacement; geophysical surveys (ERT) to reveal subsurface structures. Although the study found no direct correlation between the earthquake and the evolution of Lago Puzzo, the results provide valuable insights into the current deformation state of the sinkhole and offer projections for its potential future development. Ultimately, this research represents a significant step forward in refining hazard assessment methods for the region.

Long-term forced-use therapy after sensorimotor cortex lesions restores contralesional hand function and promotes its preference in Macaca mulatta - Warren G. Darling; Marc A. Pizzimenti; Diane L. Rotella; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Robert J. Morecraft (Experimental Brain Research, 2025)

Effect of nitrogen source and nickel concentration on green microalga Botryococcus braunii growth and its remediation potential - M. M. Areco; L. Rojas; D. G. Noseda; V. Passucci; N. Rotella; G. Curutchet (Journal of Applied Phycology, 2022)

Temporal correlations among demographic parameters are ubiquitous but highly variable across species - Rémi Fay; Sandra Hamel; Martijn van de Pol; Jean‐Michel Gaillard; Nigel G. Yoccoz; Paul Acker; Matthieu Authier; Benjamin Larue; Christie Le Coeur; Kaitlin R. Macdonald; Alex Nicol‐Harper; Christophe Barbraud; et al. (Ecology Letters, 2022)
Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, reproductive success and productivity. Correlations among demographic parameters were ubiquitous, more frequently positive than negative, but strongly differed across species. Correlations did not markedly change along the slow‐fast continuum of life histories, suggesting that they were more strongly driven by ecological than evolutionary factors. As positive temporal demographic correlations decrease the mean of the long‐run population growth rate, the common practice of ignoring temporal correlations in population models could lead to the underestimation of extinction risks in most species.

Changes in ipsilesional hand motor function differ after unilateral injury to frontal versus frontoparietal cortices in Macaca mulatta - Warren G. Darling; Marc A. Pizzimenti; Diane L. Rotella; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Robert J. Morecraft (Experimental Brain Research, 2020)

Recovery of precision grasping after motor cortex lesion does not require forced use of the impaired hand in macaca mulatta - Warren G. Darling; Robert J. Morecraft; Diane L. Rotella; Marc A. Pizzimenti; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Hongyu Zhang; Hesham Soliman; Dave Seecharan; Ian Edwards; David McNeal; Randolph J. Nudo; et al. (Experimental Brain Research, 2014)

Laterality affects spontaneous recovery of contralateral hand motor function following motor cortex injury in rhesus monkeys - Warren G. Darling; Nicole Helle; Marc A. Pizzimenti; Diane L. Rotella; Stephanie M. Hynes; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Robert J. Morecraft (Experimental Brain Research, 2013)

Satellite imagery can be used to detect variation in abundance of Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Michelle A. LaRue; Jay J. Rotella; Robert A. Garrott; Donald B. Siniff; David G. Ainley; Glenn E. Stauffer; Claire C. Porter; Paul J. Morin (Polar Biology, 2011)

Minimal forced use without constraint stimulates spontaneous use of the impaired upper extremity following motor cortex injury - Warren G. Darling; Marc A. Pizzimenti; Diane L. Rotella; Stephanie M. Hynes; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Tyler Vanadurongvan; David W. McNeal; Kathryn M. Solon-Cline; Robert J. Morecraft (Experimental Brain Research, 2010)

Tactile impairments cannot explain the effect of age on a grasp and lift task - K. J. Cole; Diane L. Rotella; John G. Harper (Experimental Brain Research, 1998)